(untitled) (Research, Society and Development, 2022)
The objective of this theoretical essay was to analyze the relationship between social participation and Brazilian democracy in recent years. Considering that Brazilian democracy is in crisis, the question is: “What are the repercussions that such a scenario brings to participatory democracy and, more deeply, to institutions of participation?”. The essay benefited from a bibliographic survey and documental research, analyzing antagonistic cases in which the social participation agenda was understood: Decree Nº. 8.243, of 2014, which strengthened and articulated democratic mechanisms and instances during the government of then President Dilma Rousseff; and Decree Nº 9.759, of 2019, which limited and extinguished collegiate bodies, of the current President Jair Messias Bolsonaro. Through the analytical-conceptual framework of Charles Tilly, it is verified that the repercussions of the Decree Nº 9.759, of 2019, comprise scenarios that precede and indicate a de-democratization movement underway in the government of President Jair Messias Bolsonaro. It is understood that Brazilian democracy does not only take place through the representative model, but also through the participatory model (networks of trust). Participation institutions cannot be excluded from political processes and public action, due to administrative rationalization and resource savings, as the current President argues.